ASUHAN KEPERAWATAN PADA BALITA INFEKSI SALURAN PERNAPASAN AKUT DENGAN HIPERTERMI MELALUI PEMBERIAN TERAPI TEPID SPONGE - Suganda Suganda; Siska Iskandar; Nengke Puspita Sari; Maritta Sari (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Bengkulu, 2022)
Problem Acute Respiratory Infection is a series of nursing actions given to overcome nursing problems in toddlers with acute respiratory infections which includes the process of assessing health problems, formulating nursing diagnoses, preparing nursing action plans, implementing nursing actions and evaluating nursing actions that have been carried out. Destination The purpose of this study was to obtain an overview of nursing care by providing tepid sponge therapy in reducing body temperature in patients with acute respiratory infections. Methodology This research is qualitative research with a case study design to explore the problem of nursing care in infants with acute respiratory infections, through a nursing care approach that includes nursing assessment, formulation of nursing diagnoses, preparation of nursing action plans (nursing interventions), implementation of nursing actions (nursing implementation), and evaluate nursing actions that have been carried out (nursing evaluation). Results Research shows that there is a decrease in body temperature after tepid sponge therapy in patients with acute respiratory infections.